(untitled) (Journal of the College of Basic Education, 2022)
In this work we shall introduce a definition of strong periodic ring and we prove some properties of this type of rings. 1. Introduction : The concept of ring is very important concept in Algebra [1],[2] . We give a definition of periodic ring where a ring is called periodic if every subring is periodic that is there exist r R such that rS=S for S subring of a ring R. And we give a definition of a strong periodic ring if rS=S for every r R . We find the intersection of two strong periodic subring is a gain strong periodic subring .we prove if R is a strong periodic ring and be ideal of R